Prevalencia del complejo Entamoeba histolytica/Entamoeba dispar en pacientes con síntomas gastrointestinales de diarrea procedentes de Cumaná, Estado Sucre - Mora Leonor; García Ana; Donato Marcos (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
Abstract: Entamoeba histolytica is considered a public health problem due to its high prevalence and its consequences for the affected individuals, and especially in children where it can cause death. Few studies of the prevalence of this parasite have been carried out in northeastern Venezuela, and for this reason feces samples from 400 patients with gastrointestinal symptoms of diarrhea, of all ages and both sexes were studied, in order to determine the prevalence of complex Entamoeba histolytica/Entamoeba dispar and its association with other parasites. Samples were analyzed copro-parasitologically using 0.85% saline physiological and lugol solution, trichromic staining, hidden blood tests and concentration tests elaborated by Ritchie. An interview was made with each participant in order to register epidemiological and clinical data. A prevalence of 16.0% (n=64) for complex Entamoeba histolytica/Entamoeba dispar was found. Other frequently observed parasites were Blastocystis hominis 19.3% (n=77), Entamoeba coli 9.3% (n=37), Endolimax nana 8.0% (n=32), Giardia lamblia 5.8% (n=23), Trichuris trichiura 4.0% (n=16), Ascaris lumbricoides 3.8% (n=15). About 15.5% of the patients showed multiparasitic infections and 37% presented only one parasite. Blastocystis hominis was the species most frequently associated with complex Entamoeba histolytica/Entamoeba dispar 10.9% (n=7). Symptoms were variable, including vomiting (26.6%), nausea (39.1%), abdominal pain (68.8%), fever (28.1%) and flatulence (65.6%). The presence of amoebas was not statistically associated with sex (χ2=0.46, p>0.05), but it was related to age (χ2=16.63, p<0.05), and the age group from 10-19 years old was the most affected. The prevalence of intestinal parasites, especially for complex Entamoeba histolytica/Entamoeba dispar, indicated that this is an important problem which needs to be addressed by sanitation authorities. Resumen: Entamoeba histolytica es considerada un problema de salud pública debido a su alta prevalencia y las consecuencias para los individuos, especialmente niños a quienes puede causar incluso la muerte. Pocos estudios se han llevado a cabo sobre la prevalencia de estas especies en el nororiente de Venezuela, por lo que se planteó analizar 400 muestras de heces de pacientes con síntomas gastrointestinales de diarrea de ambos sexos y diferentes grupos etarios para determinar la prevalencia del complejo Entamoeba histolytica/Entamoeba dispar y su asociación con otros parásitos ademàs de su asociación con algunos parámetros epidemiològicos. Las muestras fueron analizadas por métodos coproparasitológicos usando solución salina fisiológica al 0,85%, lugol, coloración tricrómica, sangre oculta y concentración por Ritchie. A cada paciente se le aplicó una encuesta para obtener datos clínicos y epidemiológicos. Se encontró una prevalencia de 16,0% (n=64) para el complejo Entamoeba histolytica/Entamoeba dispar. Otros parásitos frecuentes fueron Blastocystis hominis 19,3% (n=77), Entamoeba coli 9,3% (n=37), Endolimax nana 8,0% (n=32), Giardia lamblia 5,8% (n= 23), Trichuris trichiura 4,0% (n=16), Ascaris lumbricoides 3,8% (n=15). Un 15,5% de los pacientes estaban poliparasitados, mientras que 37,0% mostraron un único parásito. Blastocystis hominis resultó ser el parásito mayormente asociado con complejo Entamoeba histolytica/Entamoeba dispar 10,9% (n=7). La sintomatología fue variable entre los que podemos mencionar vómitos (26,6%), nauseas (39,1%), dolor abdominal (68,8%), fiebre (28,1%) y flatulencia (65,6%). No se encontró asociación significativa entre la presencia de las amibas y el sexo (χ2=0,46, p>0,05), pero sí con la edad (χ2=16,63, p<0,05), siendo el grupo etario 10-19 años el más afectado. Las cifras de prevalencia de parásitos intestinales, especialmente para el complejo Entamoeba histolytica/Entamoeba dispar, demuestran que existe un problema importante de salud que debe ser abordado por las autoridades sanitarias del estado.